EDUKASI DAN PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) CEMARA DALAM UPAYA PENCEGAHAN DEMAM BERDARAH MENGGUNAKAN SERBUK DAUN PEPAYA - Sari Wahyunita; Didik Rio Pambudi; Hasan Ismail; M. Andi Chandra; Syahrizal Ramadani; Aesty Rahayu; Wahyudi Wahyudi (Jurnal Abdimas Bina Bangsa, 2023)
Abate powder In the field, the use of abate powder is still not well controlled, because the community feels that there has been a change in the quality of the water, such as taste, smell, and color. Papaya leaves can be processed and used as a natural mosquito repellent that is safe and inexpensive. Papain contained in papaya leaves has antitoxic properties even in low doses, when enters the body of Aedes aegypti mosquito larva it will cause a chemical reaction in the body's metabolic processes which can cause inhibition of growth hormone so that the larvae can’t grow into instar IV. Even the aftermath of the inability of the larva to grow resulted in death. This activity was carried out to empower the community in the utilization of papaya leaves as a natural larvicide to prevent the spread of dengue hemorrhagic fever which is mediated by the Aedes aegypty